Liposome mediated gene transfer into the rat oesophagus. Issue 4 (1st October 1997) - Schmid, R M; Weidenbach, H; Draenert, G F; Liptay, S; Lührs, H; Adler, G
Abstract : Background —Cancer of the oesophagus has so far eluded every attempt at pharmacological treatment. The recent advent of somatic gene therapy offers a new therapeutic approach to malignant tumours. Aim —To investigate whether and how gene transfer into the oesophagus can be achieved. Methods —A LacZ reporter gene was used as marker and transferred into the oesophagus of rats using cationic liposomes. Gene transfer was achieved by either luminal instillation into a closed segment using a double balloon catheter, or by intramural injection through a needle. Expression of β-galactosidase was monitored in the oesophagus and various control tissues by histochemistry, polymerase chain reaction (PCR), reverse transcriptase PCR, and Southern blotting. Results —Up to 100 days after in vivo gene transfer β-galactosidase activity could be demonstrated in the oesophagus. Following luminal application, the transgene was expressed in epithelial cells whereas intramural injection induced preferential expression in fibroblasts. Conclusion —In vivo gene transfer into the oesophagus is feasible and safe, and the route of administration largely determines cell type specificity. This novel approach will enable in vivo studies of growth, differentiation, and malignant transformation in the oesophagus, and may open new avenues to the confinement of oesophageal malignancies.